2005
DOI: 10.1038/sj.ejcn.1602100
|View full text |Cite
|
Sign up to set email alerts
|

Netherlands Research programme weight Gain prevention (NHF-NRG): rationale, objectives and strategies

Abstract: Objective: To outline the rationale, objectives and strategies used in a systematically designed research programmme to study specific weight gain-inducing behaviours, their social-psychological as well as environmental determinants, and the effects of interventions aimed at the prevention of weight gain. Design: The evidence for potential behavioural determinants and strategies to prevent weight gain was reviewed, and the methods applied within the Netherlands Research programme weight gain prevention (NHF-NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…47 Yet, research indicates limited and selective information processing when behavior is guided by strong habits rather than intentions 46 and suggests the necessity of additional strategies be- yond merely providing information. 48 Although using past behavior as a measure of habit strength has been criticized by Ajzen, 49 Verplanken and Orbell 44 have argued that habit is a psychological construct rather than mere past behavioral frequency and have developed a script-based measure of habit to stimulate further development of habit research and theory. Empirical evidence of this measure in determinant studies of adolescent PA is lacking, but because these results indicated that intention did not significantly influence PA, one may question the tenet that adolescent physical activity is largely explained by their personal motivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Yet, research indicates limited and selective information processing when behavior is guided by strong habits rather than intentions 46 and suggests the necessity of additional strategies be- yond merely providing information. 48 Although using past behavior as a measure of habit strength has been criticized by Ajzen, 49 Verplanken and Orbell 44 have argued that habit is a psychological construct rather than mere past behavioral frequency and have developed a script-based measure of habit to stimulate further development of habit research and theory. Empirical evidence of this measure in determinant studies of adolescent PA is lacking, but because these results indicated that intention did not significantly influence PA, one may question the tenet that adolescent physical activity is largely explained by their personal motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies on physical activity determinants need to extend beyond behavioral sciences alone 54 and include environmental factors and social-cognitive factors in a single study. 17,48 Moreover, social-cognitive factors should be used to test and explain the relationship between the physical environment and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Offering respondents a choice of the behavior they prefer to focus on may favorably influence success rates in terms of health behavior change (Kremers et al, 2005). To inform intervention developers, it is important to examine the role of preferred and nonpreferred lifestyle options.…”
mentioning
confidence: 98%
“…73 Information technologies thus represent an increasingly pervasive and promising method for delivering health services and support, 74 including preventive health services, to them. 75 The globalization of population-wide mobile phone use in developing as well as industrialized nations promises to extend the potential reach of such communication platforms even further. 76 An additional facet of the "bottom up" research approach involves the explicit evaluation of the person by environment interactions in order to gain a more thorough understanding of the potential moderating effects of built and social environments on physical activity change.…”
Section: Sciencementioning
confidence: 99%